Primary eccrine porocarcinoma of the thumb with multiple metastases: a case report and review of the literature. Issue 1 (1st January 2019) - McGuire, Connor; Fadel, Zahir; Samargandi, Osama; Williams, Jason
Abstract: We present a case of primary eccrine porocarcinoma of the thumb in a 56-year-old male who ultimately developed multiple metastases. With so few cases of such lesions and their aggressive nature, accurate diagnosis and prompt surgical management is essential.